2010
DOI: 10.1136/hrt.2009.189118
|View full text |Cite
|
Sign up to set email alerts
|

Reduced left atrial function on exercise in patients with heart failure and normal ejection fraction

Abstract: HFNEF patients have reduced LA function on exercise in addition to left ventricular systolic and diastolic dysfunctions. Reduced LA function probably contributes significantly to exercise intolerance and breathlessness in HFNEF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 33 publications
5
82
1
1
Order By: Relevance
“…28 This is, particularly, important in the presence of reduced diastolic filling time because of increased heart rate, for example, during exercise, and an impairment of atrial systolic function may compromise filling and cardiac output with effort. Interestingly, late annular diastolic velocity, a measure of atrial contractility, increases in hypertensive subjects with isometric handgrip 29 and by exercise, 30 but was unchanged in HFpEF. Consequently, impaired LA contractility because of increased atrial afterload or intrinsic atrial myopathy 31 might explain reduced cardiovascular efficiency with effort in HFpEF.…”
Section: Stages Of Heart Failurementioning
confidence: 99%
“…28 This is, particularly, important in the presence of reduced diastolic filling time because of increased heart rate, for example, during exercise, and an impairment of atrial systolic function may compromise filling and cardiac output with effort. Interestingly, late annular diastolic velocity, a measure of atrial contractility, increases in hypertensive subjects with isometric handgrip 29 and by exercise, 30 but was unchanged in HFpEF. Consequently, impaired LA contractility because of increased atrial afterload or intrinsic atrial myopathy 31 might explain reduced cardiovascular efficiency with effort in HFpEF.…”
Section: Stages Of Heart Failurementioning
confidence: 99%
“…1 Left atrial (LA) dysfunction and remodeling are commonly observed in patients with heart failure (HF). Growing evidence suggests that LA dysfunction is an active contributor to symptoms [2][3][4][5] and to disease progression. 3,6,7 HF-related LA remodeling is poorly understood, and it is not known whether there are fundamental differences between HF patients with preserved (HFpEF) or reduced LV ejection fraction (HFrEF), though prior studies suggest greater adverse effects from loss of LA function in HFpEF compared with HFrEF.…”
mentioning
confidence: 99%
“…The sheer number of measures of LA function (.20) generates confusion and hinders comparability of published studies. The reproducibility of these measures may also be an issue that threatens the robustness of these B (Asymptomatic structural heart disease) † LA peak reservoir strain measured within 48 h of admission for acute myocardial infarction is associated with the composite outcome of death and HF 13 † LA function independently predicts HF hospitalization among patients with coronary artery disease and preserved LVEF 14 † LA pump function is the strongest predictor of major adverse cardiac events and all-cause mortality in patients with chronic hypertension 15 † LAEF is associated with risk of new-onset AF independent of clinical risk factors, LV systolic/diastolic function, and LA volume in elderly persons referred for echocardiography 16 † LA ejection force is associated with risk of cardiovascular events independent of age, risk factors, LV geometry, and LV diastolic function in a population with pre-clinical risk factors such as hypertension and diabetes 17 † LA strain occurs in hypertensive and diabetic patients even prior to development of overt LA dilatation 18 C (Symptomatic HF) HFpEF † LA kinetic energy predicts cardiovascular death and HF hospitalization in chronic HF regardless of EF, and has an incremental prognostic value over LA size 19 † Blunted increase in mitral annular A' velocity during exercise distinguishes HFpEF from asymptomatic hypertensive patients 20 † LAEF at rest and blunted LA systolic reserve with isometric handgrip distinguish HFpEF from asymptomatic hypertensive LV hypertrophy 21 † LA dysfunction relates to symptom onset in HFpEF 22 and occurs even in the absence of overt LA enlargement 23 † LA strain is independently associated with exercise capacity in HFpEF 24 † LA pump function is an independent correlate of HF symptoms in hypertrophic cardiomyopathy 5 …”
mentioning
confidence: 99%